Hydraulic Performance of Sharp-Crested Side Slit Weirs - Kartal, Veysi; Emiroglu, M. Emin (Springer, 2023)
A rectangular slit weir is used to measure small discharges (Q < 5 L/s) and contraction ratios (b/B <= 0.25). Various discharge relationships were reported in the literature for calcu-lating the discharge capacity of slit weirs in terms of frontal flow. However, this is not valid for lateral flow. In the current study, the side slit weir flow was investigated experimentally using piezometric heads over the weirs. The discharge coefficient was investigated for side slit weirs with different contraction ratios, which ranged from 0.075 to 0.25. Accordingly, the discharge coefficients were calculated using the Schmidt approach. Moreover, the out -flow discharge of sharp-crested side slit weir was analyzed using the incomplete self-sim-ilarity theory (ISS) and dimensional analysis. The new discharge model was theoretically created based on the experimental results obtained from laboratory tests. The results of the current study indicated that the contraction ratio, dimensionless head over the weir, and Froude number were dominant parameters over the discharge of sharp-crested side slit weirs. Within this framework, slit weirs can be used laterally as water intake structures for small discharges. Furthermore, a nonlinear equation including all effective parameters is proposed to obtain the discharge capacity of sharp-crested side slit weirs with the highest accuracy.
Keywords: Open channel flow; Self-similarity; Slit weir; Lateral flow; Side weir